A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Singh, Navneet; Volynkin, Anton V.; Kirti, Jagbir Singh; Datta, Harvinder Singh; Ivanova, Maria S. (Zootaxa, 2020)
Indian taxa of the genus Cyana Walker, 1854 are reviewed. Five new species and three new subspecies are described: C. rudloffi Volynkin & N. Singh, sp. nov., C. atlanteia N. Singh et al., sp. nov., C. chrysopeleia N. Singh et al., sp. nov., C. dohertyi eirene Volynkin & N. Singh, ssp. nov., C. britomartis N. Singh & Volynkin, sp. nov., C. arama metis Volynkin & N. Singh, ssp. nov., C. dryope Volynkin & N. Singh, sp. nov. and C. conclusa nicobara N. Singh et al., ssp. nov. The replacement name for C. tripunctata Rothschild, 1936 nec. Reich, 1935 is introduced: C. arorai Volynkin et al., nom. nov. Cyana linatula (Swinhoe, 1891), stat. rev. and Cyana watsoni Hampson, 1897, stat. rev. are restored to species rank from the synonymy with Cyana subornata (Walker, 1854) and Cyana moelleri (Elwes, 1890), respectively. Cyana paeninsulana Černý, 2009 is downgraded to a subspecies of C. selangorica (Hampson, 1903): C. selangorica paeninsulana Černý, 2009, stat. nov. Cyana flavotincta (Draudt, 1914) is downgraded to a subspecies of C. coccinea (Moore, 1878): Cyana coccinea flavotincta (Draudt, 1914), stat. nov. Five new synonyms are established: C. detrita Walker, 1854 = Lyclene tripunctata Reich, 1935, syn. nov.; C. obliquilineata (Hampson, 1900) = Cyana baolini Fang, 1992, syn. nov.; C. gelida gelida (Walker, 1854) = Lithosia alborosea Walker, 1864, syn. nov.; C. khasiana Hampson, 1897 = Chionaema hampsoni Kaleka, 2003, syn. nov.; C. arama arama (Moore, 1859) = Bizone triguttata Walker, 1869, syn. nov. The lectotypes are designated for the following 30 taxa: Cyana detrita Walker, 1854, Barsine suffundens Walker, 1864 [1865], Bizone coccinea Moore, 1878, Chionaema coccinea form flavotincta Draudt, 1914, Bizone puer Elwes, 1890, Bizone linatula Swinhoe, 1891, Cyana dudgeoni Hampson, 1895, Bizone peregrina Walker, 1854, Cyana catorhoda Hampson, 1897, Bizone quadrinotata Walker, 1869, Bizone pallens Butler, 1877, Bizone amabilis Moore, 1877, Bizone harterti Elwes, 1890, Doliche gelida Walker, 1854, Lithosia alborosea Walker, 1864, Bizone mölleri Elwes, 1890, Cyana watsoni Hampson, 1897, Bizone gazella Moore, 1872, Bizone dohertyi Elwes, 1890, Bizone sikkimensis Elwes, 1890, Cyana khasiana Hampson, 1897, Bizone bellissima Moore, 1878, Bizone arama Moore, 1859, Bizone triguttata Walker, 1869, Bizone adita Moore, 1859, Bizone bifasciata Poujade, 1886, Bizone signa Walker, 1854, Bizone fasciculata Walker, 1856, Bizone perornata Walker, 1854 and Bizone conclusa Walker, 1862.